2021
DOI: 10.1002/jca.21897
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of antibody‐mediated rejection with double‐filtration plasmapheresis, low dose IVIg plus rituximab after kidney transplantation

Abstract: Antibody‐mediated rejection (ABMR) at early or late post‐transplantation remains challenging. We performed a single‐center single‐arm study where four cases of acute ABMR and nine cases of chronic active ABMR (defined by Banff classification) were treated with double‐filtration plasmapheresis (two cycles of three consecutive daily sessions with a 4‐day gap between). At the end of the third and sixth DFPP sessions, the patients received rituximab 375 mg/m2. After a median follow‐up of 1078 (61‐1676) days, kidne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…DFPP, a semi‐selective plasma purification, avoids the unnecessary loss of plasma proteins, reduces the need for liquid replacement and increases the efficiency of purification 9,10,23 . Previous studies proved that DFPP efficiently decreased the level of DSA of kidney transplantation patients, although hypotension occurred more frequently than PE 9,12,13,24 . Our results demonstrated that DFPP treatment can decrease the levels of DSA efficiently.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…DFPP, a semi‐selective plasma purification, avoids the unnecessary loss of plasma proteins, reduces the need for liquid replacement and increases the efficiency of purification 9,10,23 . Previous studies proved that DFPP efficiently decreased the level of DSA of kidney transplantation patients, although hypotension occurred more frequently than PE 9,12,13,24 . Our results demonstrated that DFPP treatment can decrease the levels of DSA efficiently.…”
Section: Discussionsupporting
confidence: 54%
“…9,10,23 Previous studies proved that DFPP efficiently decreased the level of DSA of kidney transplantation patients, although hypotension occurred more frequently than PE. 9,12,13,24 Our results demonstrated that DFPP treatment can decrease the levels of DSA efficiently. The mean MFI values before and after treatment were 7505.88 ± 4424.38 and 2013.29 ± 4067.22 (p < 0.001) respectively.…”
Section: Discussionsupporting
confidence: 52%
“…DFPP is used for the treatment of various pathologies, depending on the target substance to be eliminated (immunoglobulins, LDL‐cholesterol or fibrinogen and clotting factors in order to improve blood rheology and tissue perfusion) 1‐10 …”
Section: Introductionmentioning
confidence: 99%